Modelo Para Medir As Relações Interinstitucionais Estratégicas Para O Desenvolvimento Organizacional: Aplicação Na Piscicultura Brasileira (Global Journal of Management and Business Research, 2023)
Study question Do inter-institutional relations favor do not favor organizational development For this purpose the following theories were used as a theoretical framework Triple Helix and Planned Behavior The cross-section was carried out in three moments of the International Fish Congress Event in 2021 in the city of Foz do Igua u PR The surveyed population consisted of 328 participants from industry university and government The data collection instrument was a questionnaire with 18 questions with Likert scale The contribution is the proposition of statistical modeling between the theory of the Triple Helix and the Theory of Planned Behavior The final construct of the model used six statistical analyses The results made it possible to suggest a plan of interinstitutional strategies for Brazilian fish farming Furthermore the plan made it possible to guide technology transfer policies the elaboration of effective normative and incentive policies and instigated the resolution of the market s sustainability needs
Keywords: triple helix planned behavior strategic planning synergies model behavior cross model